1881 Ill. Laws 73, § 2 - (:unkn) unknown (General Publisher, 1881)
Prohibited selling, giving, loaning, hiring for barter any minor a pistol, revolver, derringer, Bowie knife, dirk or other deadly weapon. Punishable by fine of $25-200.
--
Keywords: TRANSFER - MINORS